FLIGHT ATTENDANTS AND ENVIRONMENTAL TOBACCO SMOKE (Tufts Archival Research Center, 2007)
Newsletter article on the exposure of flight attendants to ETS (environmental tobacco smoke). Cites the National Academy of Sciences’ recommendation to ban smoking on all domestic commercial flights. Discusses an upcoming conference in Chicago that will serve to educate flight attendants on the risks of their profession as well as help them join forces in strategizing to implement a smoking ban.